Human behaviour : electricity consumption of multi-storey residential buildings in Shah Alam and Kuala Lumpur / Nehzat Jalalkamali - Jalalkamali, Nehzat (2014)
In the past years, the energy crisis has become more and more serious and needs to be paid more attention to accordingly. Residential sector building energy consumption uses a large portion of the Total National Energy Consumption (TNEC) all over the world. Energy consumption in residential buildings is dependent on building characteristics and occupants’ behaviour. To investigate the interaction between human behavior and the related electricity consumption, a quantitative research was conducted on a sample of 117 residents of three condominiums in The Klang Valley. The socio-demographic factors towards electricity consumption and the effect of awareness on electricity consumption were then investigated by statistical analysis. The analysis revealed that out of seven introduced independent variables (age, race, gender, monthly income, Education, Number of people staying at home and Type of Tenure), only income and number of people living in the house could significantly and positively contribute to electricity consumption. A model was suggested according to the regression analysis of the results. It was also shown that unlike the previous studies, there was no significance relationship between the type of tenure and electricity consumption. Finally the positive effect of electricity awareness on electricity consumption is shown by fee results. The comparison between the multistorey local residents’ patterns and styles of living and their relative electricity consumption with the overseas’ people might enlighten many views towards sustainable behavioural living.